Theoretical basis of biquadratic transformation - Baidabekov Ауез (Рroblems of engineering and professional education, 2023)
As a result of the analysis of scientific works on applied geometry, the quadratic transformation of the plane has been fully studied and is used in science and technology. But four-quadruple correspondences and plane biquadratic transformation theories are less studied. Therefore, this article is devoted to the development of the theory of four-four correspondences between non-facing planes and the theory of plane biquadratic transformations.